Newcastle Disease Virus Infection Promoted Bax-Mediated Apoptosis Assisted by the BH3 Domain of Matrix Protein - Molouki, Aidin (2011)
Newcastle disease virus (NDV) is a highly contagious avian paramyxovirus which leads to substantial losses in the poultry industry. NDV has gained widespread attention for its ability to selectively kill human cancer cells by apoptosis, and thus, it has been used as a cancer viro-therapeutic agent in many clinical trials. However, the exact mechanisms by which NDV induces apoptosis and kills cancer cells are still not entirely understood. Moreover, the precise signaling pathways leading to mitochondrial dysfunction are not entirely studied. In this study, the overall objective was to investigate if the intrinsic pathway is activated following NDV induced Apoptosis. Moreover, involvement of the Bcl-2 family of proteins needed to be comprehensively studied. First, the apoptotic effect of the Malaysian velogenic NDV strain AF2240 on HeLa and HT29 cancer cells was examined by DNA fragmentation and AO/PI staining. Immunoprecipitation and immunofluorescence experiments showed that NDV infection leads to a conformational change in the Bax protein and exposure of its N-terminal. Fractionation experiments showed that this change is associated with subcellular redistribution of Bax from the cytoplasm onto the mitochondria surface and subsequent release of cytochrome c. Densitometric and real-time PCR analyses revealed that the total levels of Bcl-2 and Bax proteins and mRNAs were not affected by NDV treatment, challenging previous findings that the ratio of Bax/Bcl-2 determines the fate of a cell during apoptosis. Alignment of all the protein sequences of AF2240, with those from members of the human Bcl-2 family revealed many identical regions; most notably the matrix (AF2240- M) protein, large (AF2240-L) protein and fusion (AF2240-F) proteins all contained BH3-like regions in their sequences with many shared conserved residues. To further investigate the hypothesis that the existence of the BH3-like domains in NDV viral proteins are cytotoxic, the AF2240-M and AF2240-F genes were cloned into pFLAG and pEGFP.N2 vectors and transfected into HeLa cells. The expressed proteins of these constructs promoted cell death. A mutant AF2240-M-BH3 which lacked the entire BH3 domain was then generated. Transfection of pFLAG-M-BH3 into HeLa cells showed a nearly five-fold decrease in cellular death. On the other hand, another construct which translated only 40 a.a. of the N-terminal of AF2240-M showed the same cell death rate as to that of the full-length protein, strongly suggesting that the BH3-like domain within this protein promotes apoptosis. Co-transfection and coimmunoprecipitation analyses to determine whether there is any direct interaction between AF2240-M or AF2240-F proteins with some members of the Bcl-2 family showed that the AF2240-M directly interacted with Bax protein via its BH3-domain, as the mutant proteins failed to interact with Bax. Overall, this study shows NDV contains homologs to human Bcl-2 family members that induce apoptosis. Moreover, these findings expand our understanding of how oncolytic strains of NDV kill cancer cells and suggest of a potential link between these proteins that may have occurred during early evolution.